Conversor CC-CC bidirecional de alto ganho para carregamento de baterias em uma nanorrede CC de prossumidor residencial - Queiroz, Fernando Viana da Silva (2019)
The present work aims at the application of a high gain voltage bidirectional dc-dc converter for battery charging, based on the three states switching cell. The converter used operates in boost or buck modes and will be used as an interface between a battery bank with a 96 Vdc operating voltage and a bus of the 380 Vdc, applied to a nanogrid operating in direct current for residential prossumers. The battery bank can be used to power an electric vehicle, as well as supply the dc bus, in the event of a voltage drop or failure in the primary bus. The work also elaborates constructive and protective criteria for this new type of installation, discusses the topology and digital control of the converter to be implemented, as well as its stability analysis. The proposed control aims to guarantee both the bidirectionality of the power flow of the converter circuit and the stability of the reference in steady state. A cascade digital control system was designed by means of the average current technique, whose effectiveness of the control implementation on the converter and its bidirectionality were proven and presented through simulations.